Autonomia e hierarquia em duas comunidades de escravos: Os casos George (Alabama, Estados Unidos, 1847) e Lino (Vassouras, Brasil, 1871) - Pereira de Carvalho, Fábio (2013)
This article seeks argue that the search for autonomy among slaves necessarily created hierarchies within the community where they were inserted. Through two cases compared, George in U.S. and Lino in Brazil, seeks to show that a notion of slave community was built by the social actors who were part of it